2018
DOI: 10.1021/jacs.8b10299
|View full text |Cite
|
Sign up to set email alerts
|

Potent Protein Delivery into Mammalian Cells via a Supercharged Polypeptide

Abstract: The efficient delivery of proteins into cells is needed to fully realize the potential of protein-based therapeutics. Current protein delivery strategies generally suffer from poor endosomal escape and low tolerance for serum. Here, the genetic fusion of a supercharged polypeptide, called SCP, to a protein provides a generic method for intracellular protein delivery. It allows efficient protein endocytosis and endosomal escape and is capable of potently delivering various proteins with a range of charges, size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 38 publications
0
60
0
Order By: Relevance
“…Gao and colleagues genetically fused a supercharged polypeptide (SCP) to proteins to facilitate direct intracellular transduction without requirement of additional delivery agents. 231 They found that K4tagged proteins achieved highest cellular uptake and distribution into the nucleus. For genome editing, Cas9-K4/sgRNA induced 15.2% indels in the CCR5 gene in HeLa cells.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Gao and colleagues genetically fused a supercharged polypeptide (SCP) to proteins to facilitate direct intracellular transduction without requirement of additional delivery agents. 231 They found that K4tagged proteins achieved highest cellular uptake and distribution into the nucleus. For genome editing, Cas9-K4/sgRNA induced 15.2% indels in the CCR5 gene in HeLa cells.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…However, few studies have been reported on CPP-mediated CRISPR component delivery at present. Moreover, both delivery efficiency and subsequent editing efficiency were usually at a low level of just 10-20% (Ramakrishna et al, 2014b;Yin et al, 2018b;Del'Guidice et al, 2018;Yin et al, 2019a). This likely stems from the indefinite mechanism of CPP internalization and requirement for extensive optimization for targeting each type of cargo and cell.…”
Section: Cell-penetrating Peptidesmentioning
confidence: 99%
“…The cell-penetrating peptides (CPPs) are short cationic polypeptides with 10-30 amino acids in length, which could covalently conjugate to the Cas9 protein to enable the delivery of cargoes into the cytosol through passive or active endocytic pathways. For example, the Cas9 RNP fused with a supercharged peptide called SCP could be efficiently internalized into the target cells, followed by an escape from the endosomes, and translocation into the nucleus [ 61 ]. However, the covalent strategies have underlying risks of structure alteration and bioactivity reduction.…”
Section: Non-viral Nanovectors For Crispr/cas9 Deliverymentioning
confidence: 99%